Behavioral Analysis of Malaria Incidence in the Working Area of Hebeybhulu Yoka Public Health Center, Jayapura City - Dolfinus Yufu Bouway; Elsa Destalya Pasanda; Konstantina Marthina Pariaribo (Griya Eka Sejahtera, 2026)
Background: Malaria remains a global public health concern. In Jayapura City, Hebeybhulu Yoka Public Health Center ranked second highest in malaria cases in 2024, with 2,797 cases recorded. This study aimed to analyze behavioral risk factors associated with malaria incidence in the working area of Hebeybhulu Yoka Public Health Center, Jayapura City. Methods: This analytic survey used a case-control design conducted from 10–30 September 2025. A total of 92 respondents (46 cases and 46 controls; ratio 1:1) were selected using simple random sampling with age matching between groups. Data were collected through structured interviews using a questionnaire and analyzed using univariate, bivariate (chi-square, odds ratio), and multivariate (backward LR logistic regression) tests. Results: Bivariate analysis showed that hanging clothes indoors (p=0.005; OR=3.927; 95% CI=1.583–9.743) and going outdoors at night (p=0.027; OR=3.024; 95% CI=1.218–7.510) were significant risk factors for malaria incidence, while bed net use (p=0.021; OR=0.341; 95% CI=0.145–0.798) and mosquito repellent use (p=0.027; OR=0.331; 95% CI=0.133–0.821) were significant protective factors. Multivariate analysis identified hanging clothes indoors as the most dominant behavioral factor associated with malaria incidence (p=0.015; Exp(B)=3.213; 95% CI=1.254–8.235). Conclusion: Hanging clothes indoors and nighttime outdoor activity increase the risk of malaria, while bed net and mosquito repellent use are protective. Hanging clothes indoors is the dominant behavioral risk factor in this population. Community-based interventions targeting these specific behaviors are recommended to reduce malaria transmission in the study area.